Lowering water table reduces carbon sink strength and carbon stocks in northern peatlands - Kwon, Min Jung; Ballantyne, Ashley; Ciais, Philippe; Qiu, Chunjing; Salmon, Elodie; Raoult, Nina; Guenet, Bertrand; Göckede, Mathias; Euskirchen, Eugénie S.; Nykänen, Hannu; Schuur, Edward A. G.; Turetsky, Merritt R.; et al. (Global change biology, 2022)
Peatlands at high latitudes have accumulated >400 Pg carbon (C) because saturated soil and cold temperatures suppress C decomposition. This substantial amount of C in Arctic and Boreal peatlands is potentially subject to increased decomposition if the water table (WT) decreases due to climate change, including permafrost thaw‐related drying. Here, we optimize a version of the Organizing Carbon and Hydrology In Dynamic Ecosystems model (ORCHIDEE‐PCH4) using site‐specific observations to investigate changes in CO2 and CH4 fluxes as well as C stock responses to an experimentally manipulated decrease of WT at six northern peatlands. The unmanipulated control peatlands, with the WT <20 cm on average (seasonal max up to 45 cm) below the surface, currently act as C sinks in most years (58 ± 34 g C m−2 year−1; including 6 ± 7 g C–CH4 m−2 year−1 emission). We found, however, that lowering the WT by 10 cm reduced the CO2 sink by 13 ± 15 g C m−2 year−1 and decreased CH4 emission by 4 ± 4 g CH4 m−2 year−1, thus accumulating less C over 100 years (0.2 ± 0.2 kg C m−2). Yet, the reduced emission of CH4, which has a larger greenhouse warming potential, resulted in a net decrease in greenhouse gas balance by 310 ± 360 g CO2‐eq m−2 year−1. Peatlands with the initial WT close to the soil surface were more vulnerable to C loss: Non‐permafrost peatlands lost >2 kg C m−2 over 100 years when WT is lowered by 50 cm, while permafrost peatlands temporally switched from C sinks to sources. These results highlight that reductions in C storage capacity in response to drying of northern peatlands are offset in part by reduced CH4 emissions, thus slightly reducing the positive carbon climate feedbacks of peatlands under a warmer and drier future climate scenario. Northern peatlands store >400 Pg of carbon that is subject to increased decomposition if the water table (WT) decreases due to climate change including permafrost thaw‐related drying. The land surface model, ORCHIDEE‐PCH4, was optimized based on measurements across northern peatland sites and simulations showed that lowering the WT by 10 cm (1) reduced the CO2 sink by 13 +/‐ 15 g C m‐2 yr‐1, (2) decreased CH4 emission by 4 +/‐ 4 g CH4 m‐2 yr‐1, (3) accumulated 0.2 kg m‐2 less carbon over 100 years, and (4) decreased greenhouse gas balance by 310 360 g CO2‐eq m‐2 yr‐1.